Preparation and Existing States of La/Al Co-Doped Quartz Powders. Issue 2 (February 2019) - Nie, Lanjian; Wang, Yufen; Xiang, ZaiKui; Zhang, Chenyang; Wang, Lei; Jia, Yanan; Wang, Hui; Fu, Bo; Shao, Zhufeng
Abstract: The La/Al co-doped quartz powders were prepared by solid-liquid doping method. The structure, morphology and existing states of La/Al co-doped quartz powders were measured and characterized by DSC-TG, XRD, ESEM-EDX and so on. The results show that the solid-liquid doping method can effectively ensure the uniform distribution of dopant elements for La/Al. The doped salt compounds for preparing La/Al co-doped quartz powders can be completely decomposed when calcined at 650 °C. There is a certain degree of fusion between the oxides of La/Al prepared by doping and quartz powders particles, which helps improve the inherent quality of doped quartz glass.